PENGARUH LINGKUNGAN KERJA NON FISIK, KEPUASAN KERJA DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN BIMA - Hermanto, Hermanto; Mukhlis, Mukhlis (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
This research was conducted with the aim of knowing the effect of non-physical work environment, job satisfaction and workload on the performance of the employees of the Department of Population and Civil Registry of Bima Regency. This type of research is associative using a Likert scale questionnaire as a research instrument. The population in this study were all employees at the Bima Regency Population and Civil Registry Office, consisting of 119 employees. The sample in this study were 36 employees with civil servant status at the Department of Population and Civil Registry of Bima Regency. The sampling technique used in this research is purposive sampling. data collection techniques using observation, questionnaires and literature study. Data analysis techniques use validity test, reliability test, classic assumption test, multiple linear regression, correlation coefficient, determination test, t test and f test. The results showed that the non-physical work environment, job satisfaction and workload simultaneously affect the performance of the employees of the Bima Regency Population and Civil Registry Service with a very strong level of relationship.